MINERIA DE OPINIÓN, ACCESO ABIERTO Y GOBERNANZA - Hector Nigro (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2020)
The aim of this paper is to present a new look at the research needs on opinion mining, open access to information andgovernance, where the concept of opinion mining becomes increasingly complex and complete due to the associatedtechniques and technologies, without However, as IT advances, on the other hand, the formulation of policies, laws,norms and / or regulations declines as well as the impact of the use of information in this globalized and polarized world.